COVID-19 and Its Implications for Thrombosis and Anticoagulation - Berkman, Samuel A.; Tapson, Victor F. (Seminars in Respiratory and Critical Care Medicine, 2021)
Venous thromboembolism, occlusion of dialysis catheters, circuit thrombosis in extracorporeal membrane oxygenation (ECMO) devices, acute limb ischemia, and isolated strokes, all in the face of prophylactic and even therapeutic anticoagulation, are features of novel coronavirus disease 2019 (COVID-19) coagulopathy. It seems well established at this time that a COVID-19 patient deemed sick enough to be hospitalized, should receive at least prophylactic dose anticoagulation. However, should some hospitalized patients have dosage escalation to intermediate dose? Should some be considered for full-dose anticoagulation without a measurable thromboembolic event and how should that anticoagulation be monitored? Should patients receive postdischarge anticoagulation and with what medication and for how long? What thrombotic issues are related to the various medications being used to treat this coagulopathy? Is antiphospholipid antibody part of this syndrome? What is the significance of isolated ischemic stroke and limb ischemia in this disorder and how does this interface with the rest of the clinical and laboratory features of this disorder? The aims of this article are to explore these questions and interpret the available data based on the current evidence.
Keywords: COVID-19; SARS-CoV2; thrombosis; deep venous thrombosis; pulmonary embolism; anticoagulation; inflammation; hypercoagulability; prothrombotic